Use of WhatsApp as a Platform to Promote English Oral Fluency and Accuracy: A Task Repetition Approach - Garcia-Ponce, Edgar Emmanuell; Lengeling, M. Martha; Mora-Pablo, Irasema; Conaway Arroyo, Lisa Marie (Íkala, Revista de Lenguaje y Cultura, 2023)
Nowadays, English as a foreign language (EFL) teachers needed to adapt their practices to continue teaching the foreign language with the use of different emerging technologies and online platforms. This required them to develop a greater number of digital skills to promote students’ language production and achievement. Drawing on evidence which suggests that task repetition is beneficial for developing oral production in speaking and writing tasks, this exploratory study investigates the fluency and accuracy demonstrated by seven Mexican EFL students from a state university in a monologue narrative task performed on WhatsApp following a task repetition design. Fluency and accuracy metrics show that these skills appear to fluctuate in the students during the performance of the task. Interestingly, they also suggest that only fluency increased as the weeks went by, while accuracy development was limited. These results raise questions about the dynamic nature of fluency and how it may interact with accuracy, other language dimensions, student-related factors, and the online environment.